Empowering online safety: a Child-CyberCare Mobile App approach to inappropriate content filtering in web browsing / Ros Syamsul Hamid ... [et al.] - Hamid, Ros Syamsul; Abd Halim, Iman Hazwam; Jamaluddin, Muhammad Nabil Fikri; Hashim, Muhamad Arif; Che Ismail, Nurfarah Hani (UiTM Cawangan Perlis, 2023)
The use of smartphone and digital platform increased skyrocketed over the past decade. Due to generation gap between parent and children, youth internet addiction among early adolescents seems to be increasing. Internet addiction is more likely in children who feel unsupervised, have their privacy violated, or have poor parent-child relationships. Parental supervision, involvement, and meaningful connections reduce these risks and protect children from excessive internet use. Thus, this is the reason why a mobile app that can protect early adolescents is needed. This mobile app able to track online activity, detect unwanted keywords in Google searches, and receive pop-up alerts. The app's search history lets parents address concerns. SQLite manages keyword lists and search history efficiently. Usability testing and user feedback showed app effectiveness. Participating in their children's online activities teach responsible digital behaviour and creates a safe and supportive online environment. Future work entails enhancing crossplatform compatibility, refining content detection capabilities, and implementing cloud-based synchronization. Further, integrating advanced parental controls and comprehensive reporting mechanisms will fortify the app's ability to protect children's online experiences, positioning the ChildCyberCare app as a robust tool for ensuring digital safety for children.